2014
DOI: 10.1186/1472-6882-14-384
|View full text |Cite
|
Sign up to set email alerts
|

Organic silicon protects human neuroblastoma SH-SY5Y cells against hydrogen peroxide effects

Abstract: BackgroundHydrogen peroxide (H2O2) is a toxic agent that induces oxidative stress and cell death. Silicon (Si) is a biological element involved in limiting aluminium (Al) absorption with possible preventive effects in Alzheimer’s disease. However, Si has not yet been associated with other neuroprotective mechanisms.MethodsThe present experiments evaluated in the SH-SY5Y human neuroblastoma cell line the possible role of different Si G5 (50-1000 ng/mL) concentrations in preventing cellular death induced by H2O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 45 publications
(42 reference statements)
5
23
0
Order By: Relevance
“…These results suggest that, in addition to partially blocking the hypercholesterolemic properties of dietary cholesterol, silicon induced an improvement in the antioxidant status of cholesterolfed rats. Silicon has recently been found to protect a neuroblastoma cell line from hydrogen peroxide stress (49), acting as a scavenger molecule.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that, in addition to partially blocking the hypercholesterolemic properties of dietary cholesterol, silicon induced an improvement in the antioxidant status of cholesterolfed rats. Silicon has recently been found to protect a neuroblastoma cell line from hydrogen peroxide stress (49), acting as a scavenger molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to the best of our knowledge the effect of Si in a neuronal cell model has not yet been studied. Considering our previous results (Garcimartín et al, 2014) as well as the paradoxical beneficial/deleterious effects of Si described in bibliography, we hypothesised that organic Si, a bioavailable form of Si, exerts these dual effects depending on its concentration. The objective of the present study was to evaluate the protective or deleterious effects of different concentrations of organic Si (from 50 to 20,000 ng mL À1 ) on SH-SY5Y human neuroblastoma cell line.…”
Section: Introductionmentioning
confidence: 94%
“…Si prevents Al toxicity (Birchall et al, 1989) by reducing its absorption and facilitating its excretion (Popplewell et al, 1998). Besides, our group has recently suggested (Garcimartín et al, 2014) the role of Si as a protective agent against hydrogen peroxide effects on neuroblastoma human SH-SY5Y cell line. In fact, Si partially blocks cellular damage related to oxidative stress, a known cause of cell death in neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 97%
“…Very recently our group has observed that Si protected neuroblastoma cells from H 2 O 2 aggression [8,9]. Moreover, Si increased liver Si content and improved the liver antioxidant status in cholesterol fed-aged rats [10].…”
mentioning
confidence: 98%
“…Very recently our group found that organic Si protected neuroblastoma cells from H 2 O 2 aggression [8,9] and improved the antioxidant status of aged rats fed cholesterol-enriched diets [10]. Although action mechanisms are notwell known, it has been proposed that Si among others may decrease Al bioavailability by blocking its uptake through the gastrointestinal tract [11] and by impeding reabsorption [12].…”
Section: Introductionmentioning
confidence: 99%